2022
DOI: 10.3389/fphys.2021.741317
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Endurance Exercise Training Alters Repolarization in a New Rabbit Athlete’s Heart Model

Abstract: In the present study, the effect of long-term exercise training was investigated on myocardial morphological and functional remodeling and on proarrhythmic sensitivity in a rabbit athlete’s heart model. New-Zealand white rabbits were trained during a 12-week long treadmill running protocol and compared with their sedentary controls. At the end of the training protocol, echocardiography, in vivo and in vitro ECG recordings, proarrhythmic sensitivity with dofetilide (nM) were performed in isolated hearts, and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The PFs of exercise-trained dogs had faster AP upstrokes, larger AP amplitudes, and shorter APDs than non-trained dogs in absence of ACh ( Table 2 , baseline conditions). Ionic and intracellular Ca 2+ homeostasis remodeling in response to exercise training is well known for ventricular cardiomyocytes (see Kemi et al [ 48 ], Wang and Fitts [ 49 ], and Kui et al [ 50 ], and primary references cited therein). However, although interesting, the underlying mechanism of these differences in AP parameters was not the topic of the present study and was therefore not further explored.…”
Section: Resultsmentioning
confidence: 99%
“…The PFs of exercise-trained dogs had faster AP upstrokes, larger AP amplitudes, and shorter APDs than non-trained dogs in absence of ACh ( Table 2 , baseline conditions). Ionic and intracellular Ca 2+ homeostasis remodeling in response to exercise training is well known for ventricular cardiomyocytes (see Kemi et al [ 48 ], Wang and Fitts [ 49 ], and Kui et al [ 50 ], and primary references cited therein). However, although interesting, the underlying mechanism of these differences in AP parameters was not the topic of the present study and was therefore not further explored.…”
Section: Resultsmentioning
confidence: 99%
“…Durrani's research involving 701 participants, children aged 12-16 years, found a relationship between physical activity and blood pressure (Durrani & Fatima, 2015). In another study, someone who did regular physical exercise found a decrease of 20 mmHg in systolic blood pressure and 11 mmHg in diastole (Kui et al, 2022). In addition, physical exercise was found to cardiac morphological changes that will cause aortic diameter widening accompanied by left ventricular fibrosis, improve oxidative profile and metabolic health (Dupuy et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…Fibroblasts in heart muscle hyperplasia are prone to cardiomyocyte fibrosis which, if not timely treated, will lead to more serious cardiac damage and sudden death [3]. Salvianic acid A, a bioactive compound in Salvia miltiorrhiza Bge, has been reported to exert protective effect on myocardial cells and improve microcirculation and anti-thrombosis in the treatment of cardiovascular diseases [4]. However, there are limited studies on its therapeutic effect on AMI.…”
Section: Introductionmentioning
confidence: 99%